Bimbingan Belajar SBMPTN Pada Siswa Kelas XII SMA Negeri Sukodadi - Priyasmika, Rendy; Alfan, Aris; Rohmah, Rosyidah Syafaatur (TAAWUN, 2022)
Basically, tutoring is directed to help students develop understanding and learning skills and solve learning problems. The presence of tutoring can also be an alternative solution for schools to assist students in preparation for the Joint Selection to Enter State Universities (SBMPTN). The purpose of this service is to carry out a series of work programs in the field of let's study the blank paper community, provide learning opportunities for students who want to enter college through the SBMPTN or similar entrance exams and increase the motivation and competence of students participating in guidance to meet the competencies tested at the SBMPTN. The method used is a direct approach, namely by lecture and practice. The results in this service are in the form of increasing the self-confidence and motivation of guidance students to compete in the SBMPTN and increasing student competence. This can be seen from the increased enthusiasm of students to continue studying and the results of student try outs are quite high.